MEANING OF PROFIT FOR STUDENTS OF ACCOUNTING IN RELIGIOUS BASED EDUCATION IN THE CITY OF MAKASSAR. - Tenriwaru Tenriwaru; Fadlia Nasaruddin (Universitas Islam Balitar, 2019)
This study aims to determine how perceptions of the meaning of profit are seen from the perspective of students, especially accounting students at religious-based colleges in Makassar City. The research approach used is a qualitative Interpretive approach, research that provides an opportunity to obtain a deeper understanding of profit from the perspective of the students. This study will attempt to understand how the informants own views about the meaning of profit in their life as a student. By using hermeneutic intentionalism as a data analysis technique, this study concludes four (4) meanings of profit for a student. The first meaning of profit is a motivator as seen from the motivation to start a business or venture. The second meaning of profit is an investment in the hereafter which is called alms to become an amal Jariyah which will be the same as savings in the hereafter. This charity from an economic point of view means loss, but from a religious and social perspective it will be different. The third meaning of profit is a symbiotic mutualism in the form of comfort between the seller and the buyer, no one is harmed. The fourth meaning of profit is welfare and an impression which is called the fulfillment of personal needs and the needs of others as well as an attitude of respect and appreciation. It is one form of our interactions between humans.